Problematika dan Solusi Dikotomi Ilmu - Anggun Wira Puspita; Rina Muda Siraturrahmah; Muhammad Khairul Rijal (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2018)
Science is a knowledge of a field which is arranged systematically according to certain methods that can be used to explain certain symptoms in that field. Etymologically, science comes from the Arabic Language from the word ‘ilm’ which means to understand or know. Science is not merely knowledge based on agreed theories and can be systematically tested with a set of methods that are recognized in a particular field of science. In terms of philosopy, science is formed bbecause human tray to think further about the knowledge they have. Religion is a system that regulates the rules of God Almighty and it’s rules of association relate to human association and it’s enviroment. With the relevant knowledge. And the separation of general science and religious science make negative thinking on the side of those who are more inclined in their own religious or general science. The purpose of this paper is to discuss the problems and solutions caused by the dichotomy itself to achieve an education that has a vision and mission without a grouping system accordingto the dicipline science.